(untitled) (Educational Dimension, 2024)
Information technology’s rapid development necessitates continuously updating IT professionals’ skills and competencies. This study aims to select appropriate project management ICT tools to facilitate the informal education of IT company employees. The study utilized the expert evaluation method to formulate criteria and indicators for evaluating and selecting ICT tools across six categories: communication, planning, documentation, visualization and collaboration, software development, and real-time presentation feedback. Experts from leading IT companies assessed and ranked the proposed ICT tools based on the established criteria. The results identified Microsoft Teams for communication, Microsoft Project for planning, Microsoft 365 suite for documentation, Mural for visualization and collaboration, Azure DevOps for software development, and Mentimeter for real-time presentation feedback as the most suitable tools for informal education in IT companies. The selected ICT tools constitute a comprehensive toolkit to streamline educational activities and enhance informal learning experiences for IT professionals. The findings provide a foundation for implementing informal education programs within IT company resources, leveraging the selected project management ICT tools.